2008
DOI: 10.1021/jp803565k
|View full text |Cite
|
Sign up to set email alerts
|

Platinum/Mesoporous WO3 as a Carbon-Free Electrocatalyst with Enhanced Electrochemical Activity for Methanol Oxidation

Abstract: A new type of carbon-free electrode catalyst, Pt/mesoporous WO3 composite, has been prepared and its electrochemical activity for methanol oxidation has been investigated. The mesoporous tungsten trioxide support was synthesized by a replicating route and the mesoporous composties with Pt loaded were characterized by using X-ray diffraction (XRD), nitrogen sorption, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDS) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 47 publications
3
63
0
1
Order By: Relevance
“…Previous studies have shown that Pt and Pt-Ru catalysts supported on WO 3 have a high activity towards the electrooxidation of methanol and hydrogen. [20][21][22][23][24] Cui at el. [24] synthesized the meso-structured WO 3 as an anode catalyst support and they found that the catalyst showed high electrocatalytic activity for hydrogen electrooxidation and exhibited much improved resistance to Durability is an important issue in proton-exchange membrane fuel cells (PEMFCs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Pt and Pt-Ru catalysts supported on WO 3 have a high activity towards the electrooxidation of methanol and hydrogen. [20][21][22][23][24] Cui at el. [24] synthesized the meso-structured WO 3 as an anode catalyst support and they found that the catalyst showed high electrocatalytic activity for hydrogen electrooxidation and exhibited much improved resistance to Durability is an important issue in proton-exchange membrane fuel cells (PEMFCs).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidations of olefins to epoxides are also readily accessible in the presence of WO 3 catalysts and peroxide, [23][24][25][26] and semiconducting WO 3 serves as a very efficient catalyst in photochemical and electrochemical oxidation reactions. [27][28][29] Despite success in these applications, catalysts containing mostly WO 3 have been limited in gasphase thermal oxidations of alcohols with O 2 or air as the only oxidant. The poor alcohol oxidation reactivity of pure WO 3 may be attributed to the non-labile lattice oxygen atoms of WO 3 under catalytic conditions that favor dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten oxides (predominantly WO3) were studied for quite a long time as a catalyst for DMFC and showed high catalytic activity toward methanol oxidation reaction, possibly due to the formation of tungsten bronzes favoring the dehydrogenation of methanol, and a synergistic effect leading to CO tolerance [56][57][58]. Park et al [59] showed excellent performance for the use of porous tungsten oxide in thin film fuel cells and also showed good stability in sulfuric acid.…”
Section: Tungsten Oxidementioning
confidence: 99%